Підводні дослідження пам’яток західного узбережжя Криму експедицією Центру підводної археології Київського національного університету ім. Тараса Шевченка - Кобець, В.Д. (Археологічні дослідження в Україні, 2009)
The article is devoted to the summation of underwater archaeological work during 2006—2008 on the west coast of the Crimea (the cape Tarkhankut, Yevpatoria). The research was conducted by the expedition of the Centre of Underwater Archaeology together with the students and masters of the Archaeology department of T. Shevchenko Kyiv National University.